Examining volatility spillovers among ESG compliant large, mid, and small-cap stocks - Ndzamela, Xolela (Rhodes University, 2026)
Several crises have had and continue to have permanent effects on global governance and sustainable finance. These crises, however, have also raised investors’ scrutiny of firms’ Environmental, Social, and governance (ESG) performance when making investment decisions. These investment decisions have an impact on the overall market behaviour and stock volatility. Hence, with the assumed benefits of ESG adoption being believed to be a mitigating factor against stock crashes and hence volatility. It is no surprise that adopting sustainable practices has become a transformative trend in the financial sector, increasingly influencing investment decision-making. In an era where ESG principles are reshaping financial markets, adherence to ESG standards could reduce market volatility between firms of different sizes. This study aimed to examine the volatility spillovers among ESG compliant large, mid, and small-cap stocks in the US and UK markets. The methodology proposed in this paper consisted of several steps to systematically investigate the directionality, magnitude, and persistence of volatility transmissions between ESG-compliant large-, mid-, and small-cap firms in US and UK markets and to shed light on diversification and risk management. Weekly closing price data of highly compliant ESG firms that covered a span of 5 years from 5 January 2018 to 30 December 2022 were used, resulting in 261 observations. The study applied rigorous econometric models such as the principal component analysis (PCA) to create the return indices (Large, Mid and small) for both the US and UK respectively. Subsequently, the GARCH-family of models that is the GARCH (2,1) & (1,1) in as well as the TARCH (1,1) were used to generate the volatility variables using the return indices. Finally, a VAR framework was employed to analyse the volatility spillover between the large, mid and small cap volatility indices for both the US and UK respectively. The findings of the granger causality test revealed bidirectional spillovers between the large-cap and small-cap volatility index, as well as between the mid-cap and small-cap volatility index, are evident in both the US and UK markets. Unidirectional spillovers, however, differ between the two markets. In the US, the mid-cap volatility index significantly drives the large-cap volatility index. Conversely, in the UK, a top-down spillover is observed, with the large-cap volatility index influencing the mid-cap volatility index. Furthermore, the impulse response revealed that overall, in the US the midcap volatility index and in the UK the large cap volatility index has the biggest magnitude and most persistent spillover effect on other indices, transmitting positive volatility. Finally, the variance decomposition revealed in the US that the large and small caps' variance is predominately driven by shocks emanating from the mid-cap volatility index, while the mid-caps variance is driven by its own shocks. Whereas in the UK the mid and small caps' variance is predominately driven by shocks emanating from the large-cap volatility index, while the large-caps variance is driven by its own shocks. The implication of findings may suggest that ESG credentials genuinely guide investors into calmer financial waters. This is because the US mid-cap and UK large-cap are relatively insulated from volatility spillovers from other indices and serve as sources of self-reinforcing segments. This limited exposure to market-wide shocks means that changes in price movements in the markets that are mainly the recipients of volatility tend not to induce price movements in the markets that are drivers of volatility. With this, investors can shelter themselves from market risk exposure and achieve better diversification opportunities when they invest in these two self-reinforcing segments.
a comparative analysis of the US and UK markets
Keywords: Uncatalogued